Convenience bankingn ; Woman, you've come a long way ; Mrs. Fields [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1995)
Looks into the banking service called ATM (Automated Teller Machine) with its transaction fees ; women today with their evolving newer and more challenging roles and Mrs. Fields with her cookie business with 600 brank, a multi-dollar empire in only 19 years.
VHS.
Reporters, Marga Ortigas, Cheche Lazaro, Luchi Cruz Valdez.
Keywords: Fields, Deby; Automated tellers -- Evaluation; Baked products industry; Bakers and bakeries; Banks and banking -- Equipment and supplies; Industrial management -- Philippines; Women -- Employment -- Philippines; Women -- Social conditions. -- Philippines